Occupational adjustment and its relationship to organizational loyalty among the workers of the Sonelgaz Corporation in Laghouat - a field study - - - Said REIACHE; Mohamed Tahar NAKMOUCHE (Social Sciences Journal, 1970)
This study aimed to identify the relationship between the professional compatibility andorganizational loyalty in selected groups of workers at Sonelgaz company inLaghouat city, ,also aimed to find out the differences in professional compatibility in light of theintermediatevariables (social status, socio-professionalclass, and the service duration) . The Descriptivemethod of research has beenfollowed in this studythat fits with the nature of the subject on asample of (96) worker, who have been selected in a random sample, also this study used twoCriteriaare the compatibility professional Criterion, of Abdullah Abdul Aziz Samari (2010),and the organizational loyalty Criterion by the student researcher, so a number of variousmethods has been used in the statistical processing (the average, standard deviation, thePearson correlation coefficient, Guttman correlation coefficient, Cronbach's alphacoefficient, analysis of variance, T test, and then applying the SPSS17 for the statisticalanalysis).The results of the study concluded: There is a positive relationship between positivecompatibility professional and organizational loyalty at Sonelgaz,There are no statisticallysignificant differences among Sonelgaz workers in vocational compatibility attributed in lightof (social status, socio-professionalclass, and the service duration)